Teachers’ use of questions and the science/religion encounter: Basil Bernstein and the impossibility of the unthinkable - Revell, Lynn (Journal of Religious Education, 2024)
This article examines the teaching of creation in a year six and a year three Religious Education (RE) class in schools in the south of England with a focus on the type and role of teacher questioning in relation to classroom discussions. The nature of knowledge, curriculum content and the relationship between RE and other subjects is currently under scrutiny and there is an ongoing debate about the negative effects of presenting science and religion as epistemically siloed. This paper presents an analysis of the way two teachers in two primary schools used questions to frame the relationship between science and religion where the aim was to minimise the polarisation of religion and science. Using Bernstein’s idea of the pedagogic device and the related notions of frame, classification and the unthinkable the analysis suggests that teachers employed both visible and invisible pedagogies that limited the diversity of ideas that were considered legitimate in discussions, and which therefore influenced the nature of pupil questions and responses. We suggest that despite attempts by both teachers to diminish the strong boundaries between different types of knowledge their use of questions serves to reinforce them.